The Relationship Between Parental Violence and Children’s Depression with Emphasis on Psychological Mechanisms - Samaripour, Hayat; Askary, Parviz; Bozorgbashar, Jamileh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The objective of this study was to examine the relationship between parental violence and children’s depression, with specific emphasis on the predictive role of parental mental health.Methods and Materials: This study employed a correlational descriptive design with a sample of 400 children aged 8–14 years and their parents in Tehran, selected through multistage cluster sampling. Standardized instruments were used: the Children’s Depression Inventory (CDI) to measure children’s depression, the Conflict Tactics Scale – Parent Form (CTS) to assess parental violence, and the General Health Questionnaire (GHQ-28) to evaluate parental mental health. Data analysis was performed using SPSS version 27. Descriptive statistics were calculated, and Pearson’s correlation coefficient and multiple linear regression analysis were applied to test the relationships among variables at a significance level of p < .05.Findings: The results indicated that children’s depression was positively correlated with both parental violence (r = .46, p < .01) and parental mental health problems (r = .52, p < .01). Parental violence and parental mental health were also significantly correlated (r = .41, p < .01). The regression model was significant (F(2, 397) = 117.52, p < .001), explaining 37% of the variance in children’s depression (R² = .37). Both parental violence (B = 0.29, β = .31, t = 5.82, p < .001) and parental mental health (B = 0.41, β = .38, t = 6.72, p < .001) emerged as significant predictors, with parental mental health showing a slightly stronger predictive effect.Conclusion: The findings highlight that both parental violence and parental psychological distress significantly contribute to the development of depressive symptoms in children. These results underscore the importance of family-based interventions that simultaneously address violent parenting practices and enhance parental mental health to reduce the risk of depression in children.